Aplicações de zinco e boro em milho cultivado em Cambissolo da Chapada do Apodi-CE - Moreira, Vanessa Ohana Gomes (2017)
Micronutrients are essential elements in plant nutrition and the lack of these elements may directly affect agricultural production. The objective of this study was to determine the effect of increasing doses of zinc and boron in maize, cultivated in the Haplic Cambisol of Apodi - CE, on nutrient uptake (N, P, K, Ca, Mg, B and Zn); Plant height; and mass production green and dry. Two experiments were carried out in a completely randomized design during a period of 50 days after seed germination (DAE). The experiment I consisted of the application of zinc doses (Zn1 = 0 mg kg-1 , Zn 2 = 2 mg kg-1 , Zn 3 = 4 mg kg-1 and Zn 4 = 6 mg kg-1 ) and experiment II in the application of (B1 = 0 mg kg-1 , B2 = 1 mg kg-1 , B3 = 2 mg kg-1 and B4 = 3 mg kg-1 ) with four replicates for each dose. Each experimental plot consisted of a pot with 5 dm3 of soil, with three plants/pot. At the end of the experiment the plant height, mass green and dry of the aerial part and accumulation of N, P, K, Ca, Mg, Zn and B as a function of the treatments. Fertilizers with Zn significantly increased the height and yield of green and dry mass of the aerial part of the corn, and in the treatment with the highest dose (6 mg kg-1 ) there was a decrease in these variables. In relation to nutrient absorption, the increment of the doses caused significant differences (P0,01) only for the contents of P and Zn in the dry mass. Boron doses significantly increased the height and the yield of fresh and dry mass of the aerial part of the corn cultivated in pot. In relation to the nutrient absorption, the treatments caused a significant difference, (P0,01), for the accumulated contents of N, P, K, Mg and Zn and B in the dry mass. It was concluded that in experiment I, there was a significant effect on the absorption of P and Zn, and the higher Zn dose caused a depressive effect on maize growth and biomass accumulation. In relation to experiment II, with the increment of boron doses, there was a significant effect on the absorption of all analyzed nutrients with the exception of Ca and an increase in the height and accumulation of biomass of the plants.